2019
DOI: 10.1038/s41598-019-52461-6
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemotherapy induces tumor regression and decreases the proliferative index in canine cutaneous squamous cell carcinoma

Abstract: Canine cutaneous squamous cell carcinoma (cSCC) is the most common skin cancer in dogs, and, due to its low metastatic rate, local treatments, such as electrochemotherapy (ECT), promote disease control or even complete remission (CR). This study aimed to evaluate the gene and protein expression of Bcl-2 and Bcl-2 associated X protein (BAX), the proliferative index and clinical parameters in dogs with cSCC subjected to ECT. A prospective nonrandomized clinical study was performed using dogs with naturally occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 64 publications
3
20
1
Order By: Relevance
“…However, due to complete remission in some cases and owner decisions in other cases, we were not able to perfom this evaluation. Previously, our research group observed that this therapy induced a decrease in the proliferation index and tumor volume 21 days after treatment in dogs with cSCC treated with ECT 36 ; future studies evaluating tissue samples in feline cSCC could provide new valuable information.…”
Section: Discussionmentioning
confidence: 95%
“…However, due to complete remission in some cases and owner decisions in other cases, we were not able to perfom this evaluation. Previously, our research group observed that this therapy induced a decrease in the proliferation index and tumor volume 21 days after treatment in dogs with cSCC treated with ECT 36 ; future studies evaluating tissue samples in feline cSCC could provide new valuable information.…”
Section: Discussionmentioning
confidence: 95%
“…In 2019, Willcox et al (2019)reported that a retrospective study of 193 different dog breeds found dermal SCC on neck (18%), periarticular (25%), and perianal (11%) areas (Willcox et al, 2019). The same year saw reports on cutaneous cases in mixed-breed dogs, American pit bulls, boxers, and English pointers (Dos Anjos et al, 2019). From 2020 to 2021, there were reports of SCC in the cranium and oral cavity (Simčič et al, 2020;Łojszczyk et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Squamous cell carcinoma (SCC) originates from squamous epithelium, and is a malignant tumor (Willcox et al, 2019). This type of tumor in dogs has been reported in several organs, such as the cranium, cornea, rostral nasal septum, and oral cavity, while it has also occurred cutaneously (Dos Anjos et al, 2019;Simčič et al, 2020;Łojszczyk et al, 2021). Furthermore, SCC has been reported in other species, including cats, horses, and chinchillas (Thomson, 2007;Morrison et al, 2019;Szabo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to cutaneous SCC in humans, in dogs, it is usually locally invasive with low metastasis occurring late in the course of the disease, mainly to regional lymph nodes [13][14][15]. Due to its low metastasis risk, local treatments, such as surgery, cryosurgery, radiotherapy, and electrochemotherapy (ECT) are often able to provide local control, especially when initiated in the early stages of the disease and extends the survival time in most cases [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%